The efficiency in Thai financial sector after the financial crisis - Supachet Chansarn (Colegio de Economistas de A Coru\~na, 2007)
This study aims to investigate the efficiency in Thai financial sector after the financial crisis (1998 - 2004) by looking at the total factor productivity (TFP) growth. Furthermore, the study also investigate the efficiency in commercial bank sector, finance and securities company sector and insurance company sector, and the efficiency in domestic and foreign financial companies. Based on the sample of 12 commercial banks, 13 finance and securities companies and 20 insurance companies listed on the Stock Exchange of Thailand (SET) over the period of 1998 - 2204, our findin reveals that the efficiency in Thai financial sector, commercial bank sector and finance and securities company sector was diminishing over the period of 1998 - 2004, while the efficiency in insurance company sector remained unchanged over the same period. However, the sharp decrease in efficiency was decreasing very slightly over the period of 1998 - 2004. The study also suggests that, in overall, domestic financial companies are more efficient than foreign ones. Domestic finance and securities companies are also more efficient than foreign ones, whereas domestic and foreing commercial banks are not different in efficiency, Moreover, domestic and foreign insurance companies are not different in efficiency as well.
Keywords: 330; Finanzsektor; Finanzmarktkrise; Produktivität; Thailand